A Survey on Challenges, Trends and Technologies of Internet of Things - Akhila , J; Lakshmi, Ananya; Ashritha , B; Jayashree , P; Raghavendra , S; Katagall, Raghavendra (International Journal of Computer Sciences and Engineering, 2019)
This paper is a documentary survey on different areas in which Internet of Things (IoT) can be applied. Many concepts are also discussed on different IoT architectures along with several examples. This paper examines architecture of high level, conceptual levels for the IoT from a computational perspective. The paper also includes discussion about how the communication is established between IoT setup and the application. Different types of protocols to be implemented for the communication is also explained. By deploying these IoT systems the vision of smart city can be achieved. Many of the physical objects of the world are connected with sensors and actuators, which are linked by communication infrastructures and managed by computer algorithms. IoT sensor networks and integrated systems connect intelligent objects. These systems revolutionize the way we deal with our daily lives, medical care, energy and transport. These computational systems are addressed with a variety of different models and structures. In an effort to consolidate the use of these models, this document reviews research in IoT computing.